The Study of Differences and Influences of Teacher Communication and Discipline Characters of Students - Alfauzan Amin; Alimni Alimni; Dwi Agus Kurniawan; Sabila Eka Septi; Miftahul Zannah Azzahra (Jurnal Ilmiah Sekolah Dasar, 2021)
Islamic education is one of the subjects related to the formation of the character of students in schools. However, in the formation of student discipline character is still less attention and development. One way to form a good student discipline character is to connect teacher communication and student discipline character so that students can have good discipline character. Therefore, the authors conducted research related to teacher communication and student discipline character in learning Islamic religious education. The purpose of this study was to determine the comparison and influence of teacher communication variables and the disciplined character of elementary school students. This type of research uses mixed research methods with an explanatory design. Mixed methods research is a combination of quantitative research methods and qualitative research methods. This research was conducted by distributing questionnaires and interviews. The data analysis technique used is random sampling. The research subjects in this study were 80 students in elementary schools. The results obtained are elementary school 9 Jambi City has a higher percentage than elementary school 9 Bengkulu City so that elementary school 9 Jambi City has advantages in teacher communication and student discipline character. The conclusion of this study is that there is a comparison and influence of teacher communication and student discipline character.